Forecasting Oil Futures Prices Using Artificial Intelligence - Ibragimov, Rustam (2023)
Over the last couple of decades, artificial intelligence has gained popularity across different fields, including finance, marketing, medicine etc. Utilizing artificial intelligence in finance could work as a good decision-making tool in terms of analyzing both fundamental and technical factors including analyzing the sentiment of the market. The thesis aims to explore oil market, describe it from a historical point of view, introduce the most comprehensive techniques in time series prediction and sentiment analysis, create forecasts of returns of oil futures, and evaluate the performance of each of the model.